The Viscous Dissipation Effects on the Mixed Convection Boundary Layer Flow on a Horizontal Circular Cylinder - Muhammad Khairul Anuar, Mohamed; Mohd Zuki, Salleh; Nor Aida Zuraimi, Md Noar; Anuar, Ishak (Penerbit Universiti Teknologi Malaysia, 2016)
Present study consider the mathematical modeling for mixed convection boundary layer flow and heat transfer on a horizontal circular cylinder with viscous dissipation. The transformed partial differential equations are solved numerically by using an implicit finite-difference scheme known as the Keller-box method. Numerical solutions are obtained for the reduced Nusselt number, the local skin friction coefficient, the velocity and temperature profiles. The features of the flow characteristics for various values of the Prandtl number, Eckert number and mixed convection parameter are discussed. The results in this paper is original and important for the researchers working in the area of boundary layer flow and this can be used as reference and also as complement comparison purpose in future.